Measurement of Lipid Profile, LDH, Spo2 and Heart Rate in COVID-19 Patients Associated with Cardiovascular Problems in Thi Qar Province - abd, Mohammed Mahdi (Indonesian Journal on Health Science and Medicine, 2025)
The study aims to investigate the physiological characteristics of COVID-19 patients, considering demographic factors such as gender, age, infection severity, and associated cardiovascular complications. This is particularly relevant as several clinical trials have established a correlation between COVID-19 and cardiovascular disease, a grave illness that has impacted individuals globally. The study recruited 142 COVID-19 patients and 50 control individuals from hospitals and isolation centers in Thi Qar Province. Patients were categorized based on infection severity, with 54 moderate, 53 severe, and 35 critical cases. The findings reveal that 60.6% of patients were male, and the majorities (50%) were between 50-69 years old. Patients experienced various cardiovascular complications, including myocardial infarction (5.6%), arrhythmia (4.2%), heart failure (2.8%), and pulmonary embolism (2.8%), with 3.5% experiencing more than one adverse event.Compared to the control group, COVID-19 patients had significantly higher lactate dehydrogenase (LDH) concentrations and heart rates, but lower levels of total cholesterol (TC), high-density lipoprotein (HDL), low-density lipoprotein (LDL), triglycerides (TG), and oxygen saturation (SPO2). The study also identified gender and age-related differences in these parameters, highlighting the importance of considering individual characteristics when assessing the impact of COVID-19 on cardiovascular health. Highlights: COVID-19 patients showed increased LDH and heart rates but lower cholesterol and oxygen saturation levels. Gender, age, and infection severity influenced cardiovascular health outcomes in patients. The study emphasizes personalized approaches to manage COVID-19-related cardiovascular risks. Keywords: COVID, LDH, Lipid Profile, Spo2, Cardiovascular Disease.